A Tool to Improve Accuracy of Parental Measurements of Preschool Child Height - Meredith Yorkin; Kim Spaccarotella; Jennifer Martin-Biggers; Carolina Lozada; Nobuko Hongu; Virginia Quick; Carol Byrd-Bredbenner (Advances in Public Health)
Background. Parent-reported measurement of child height is common in public health research but may be inaccurate, especially for preschoolers. A standardized protocol and tools to improve measurement accuracy are needed. The purpose of this study was to develop and test materials to improve parents’ accuracy when measuring their preschooler’s height. Methods. In Phase A, 24 parents were observed measuring child height using written instructions and an easy-to-read tape measure; after each of 3 testing rounds, instructions were refined based on observed errors and parent versus researcher measurements. In Phase B, a video replaced written instructions and was refined over 4 rounds with 37 parents. Results. The height kit with written instructions, tape measure, plumb line, and explanatory video helped parents accurately measure child height. Compared to written instructions alone, parents rated the video as having significantly greater clarity and likelihood of improving measurements. Although no significant differences in accuracy were found between paper and video instructions, observations indicated written instructions were more difficult for parents with less education to use with fidelity. Conclusions. The kit may improve parent measurement of preschooler height, thereby improving accuracy of body mass index calculations, tracking of obesity prevalence, and obesity prevention and treatment.